Sistem Keamanan Lingkungan Kampus Berbasis IOT dengan Mikrokontroler Esp32 Dan Aplikasi Berbasis Web - Ridho, Yusuf; Samsugi, Selamet; Megawati, Dyah Ayu (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
This research aims to develop an Internet of Things (IoT)-based environmental security sistem utilizing microcontrollers in the campus environment. The research background arises from the increasing criminal cases in this area, emphasizing the necessity for innovative solutions to enhance the safety of the academic community. Employing a mixed-methods approach, this study integrates the analysis of criminal data, surveys, and interviews with the entire academic community to comprehensively outline the security conditions. In-depth understanding of crime patterns is derived from the analysis of criminal data, while surveys and interviews offer direct insights from participants regarding security and criminal risks. Building upon these findings, the author designs, prototypes, and tests an IoT-based security sistem integrated with microcontrollers. The test results demonstrate the sistem's effectiveness in disseminating and controlling campus environmental security. The analysis of implementation outcomes provides a comprehensive overview of the positive impact of the sistem on security levels in the area. The discussion involves interpreting results, establishing connections with existing literature, and bridging theoretical and practical implications. Therefore, this research not only contributes theoretically to security and IoT literature but also provides practical insights to enhance security, particularly in the campus environment.